1999
DOI: 10.1128/jb.181.4.1156-1162.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Transduction Protein GlnK Is Required for NifL-Dependent Nitrogen Control of nif Gene Expression in Klebsiella pneumoniae

Abstract: In Klebsiella pneumoniae, transcription of the nitrogen fixation (nif) genes is regulated in response to molecular oxygen or availability of fixed nitrogen by the coordinated activities of the nifA and nifL gene products. NifA is anif-specific transcriptional activator, the activity of which is inhibited by interaction with NifL. Nitrogen control of NifL occurs at two levels: transcription of the nifLA operon is regulated by the global ntr system, and the inhibitory activity of NifL is controlled in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 57 publications
5
92
0
1
Order By: Relevance
“…In the presence of O 2 , however, NifL appears to be oxidized directly by O 2 and dissociates from the membrane [21]. Concerning the nitrogen signal transduction, it is known that uridylylated GlnK transduces the signal of nitrogenlimitation to the nif regulon [8][9][10]21]. Experimental data indicate that under nitrogen-limitation, GlnK interacts with the inhibitory NifL-NifA complex, resulting in the dissociation of the complex (J. Stips and R. A. Schmitz, unpublished observation).…”
Section: Carbon and Energy Sourcementioning
confidence: 99%
“…In the presence of O 2 , however, NifL appears to be oxidized directly by O 2 and dissociates from the membrane [21]. Concerning the nitrogen signal transduction, it is known that uridylylated GlnK transduces the signal of nitrogenlimitation to the nif regulon [8][9][10]21]. Experimental data indicate that under nitrogen-limitation, GlnK interacts with the inhibitory NifL-NifA complex, resulting in the dissociation of the complex (J. Stips and R. A. Schmitz, unpublished observation).…”
Section: Carbon and Energy Sourcementioning
confidence: 99%
“…Both EcGlnK and KpGlnK proteins have high sequence identity to EcPII. However, EcPII expressed from the chromosome is unable to substitute for the GlnKs with respect to NifLA [13,16] . This protein was called GlnK because it has higher identity to EcGlnK than EcPII and it is encoded by a glnK gene which is located on the glnKamtB operon.…”
Section: The T-and C-loopsmentioning
confidence: 99%
“…Jack et al [16] aligned PII and parologue proteins from several organisms and found five residues (positions 3, 5, 52, 54 and 64), which distinguish GlnK from PII proteins. PII proteins contain Lys3, Glu5 or Asp5, Met52 or Val52, Asp54 and Val64.…”
Section: Relationship Of Pii To Glnkmentioning
confidence: 99%
“…PII-like nitrogen sensory proteins have been demonstrated to play a major role in regulating nitrogen metabolism and are considered to be the most widespread signalling proteins in nature [25][26][27]. Recent studies have revealed that the nitrogen status in the diazotrophs K. pneumoniae and Azotobacter vinelandii is transduced towards the regulatory proteins NifL and NifA by the PII-like protein GlnK, a GlnB paralogue [14,17,[28][29][30][31][32]. By contrast to the glnK gene of A. vinelandii, enteric glnK genes are under the control of the general nitrogen regulatory system, and are therefore only expressed under conditions of nitrogen starvation [25,33,34].…”
mentioning
confidence: 99%
“…However, in response to the internal nitrogen status, GlnK is covalently modified by uridylylation, as is GlnB at the conserved tyrosine residue located in the T-loop (Y51), by the uridylyltransferase ⁄ uridylyl-removing enzyme GlnD [25,35,36]. It has been demonstrated that GlnK mediates the cellular nitrogen status towards the NifL ⁄ NifA regulatory system by direct protein interaction; however, the mechanism differs between K. pneumoniae and A. vinelandii [14,17,[28][29][30][31][32]. In A. vinelandii, the nonuridylylated form of GlnK activates the inhibitory function of NifL under nitrogen excess by direct protein-protein interaction [37,38], whereas, under nitrogen limitation, NifA is relieved from NifL inhibition by elevated levels of 2-oxoglutarate binding to the GAFdomain of NifA [4,14,18,32,[37][38][39][40][41].…”
mentioning
confidence: 99%